in Set Theory & Algebra
4,692 views
26 votes
26 votes

If $g(x) = 1 - x$ and $h(x) = \frac{x}{x-1}$, then $\frac{g(h(x))}{h(g(x))}$ is:

  1. $\frac{h(x)}{g(x)}$
  2. $\frac{-1}{x}$
  3. $\frac{g(x)}{h(x)}$
  4. $\frac{x}{(1-x)^{2}}$
in Set Theory & Algebra
by
1433 1865 2328
4.7k views

2 Comments

Please edit the question! Correct question is given below:

6
6
Thanks. Edited :)
2
2

Subscribe to GO Classes for GATE CSE 2022

3 Answers

32 votes
32 votes
 
Best answer
option a) is correct.

$g\left(h\left(x\right)\right) =g\left(\frac{x}{x-1}\right)$
    $=1-\frac{x}{x-1}$
    $= \frac{-1}{x-1}$

$h\left(g\left(x\right)\right) =h(1-x)$
  $=\frac{1-x}{-x}$

$\frac{g(h(x))}{h(g(x))} = \frac{x}{(1-x)(x-1)} = \frac{h(x)}{g(x)}$
       

option A)
edited by
by
10 23 35

4 Comments

sir how iitk declare ans as a?
0
0
Answer is A only. I guess the answer was put for a different question- corrected now :)
1
1
But why is the answer not D then?
0
0

 @ hope you get this now

 

1
1
0 votes
0 votes
Correct answer is A because of

(x/x-1)*(1/1-x)

g(x) = 1-x and h(x)=x/x-1

so h(x)/g(x)
by
11 61 134
–1 vote
–1 vote

The correct answer is (A) h(x) / g(x)

by
25 70 138
Answer:

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true